Peningkatan Pemahaman Konsep Kolaborasi Antar Budaya di Indonesia pada Peserta Didik Melalui Media Pembelajaran Poster Digital - Rifki Ramzan Adi Putra; Yunisca Nurmalisa; Devi Sutrisno Putri (Jurnal Kewarganegaraan, 2024)
This research aims to determine the application of the use of digital poster learning media in increasing students' understanding of the concept of intercultural collaboration in Indonesia. The research method used in this research is quasi-experimental with a quantitative approach. The subjects of this research were students at SMAN 2 Pringsewu. The sample in this study amounted to 70 respondents consisting of 35 experimental class respondents and 35 control class respondents. The data analysis technique uses descriptive statistical analysis which is used to describe research data in the form of students' understanding of PPKn learning as a result of using digital poster learning media in the experimental class and whiteboard media in the control class. Based on the results of research conducted by researchers, there are differences in understanding of identity material and cultural collaboration among students who apply digital poster learning media (experimental class) as proven by the N-Gain Score analysis test. Learning in the experimental class is more interactive compared to the control class as seen from the number of students who ask questions, answer questions, listen to the teacher's explanation, explain and give examples and conclude the material being studied. The posttest results of the experimental and control classes experienced differences where the results of the experimental class were superior to those of the control class. Students' understanding of identity material and cultural collaboration in the experimental class with digital poster learning media was categorized as effective, while those in the control class which used blackboard learning media were categorized as ineffective. Kata Kunci: Understanding. Learning Media, Digital Posters.